A brief review of choice bundling: A strategy to reduce delay discounting and bolster self-control. (June 2020) - Ashe, Melinda L.; Wilson, Stephen J.
Highlights: Delay discounting shows underweighting future outcomes contributes to addiction. Choice bundling, aggregating decisions, could combat excessive discounting. Future tests of bundling should incorporate realistic contingencies and costs. Future tests of bundling should be conducted outside of the laboratory. Abstract: Choice bundling is a behavioral economic strategy designed to reduce excessive delay discounting and bolster self-control. Choice bundling entails aggregating a series of individual, identical intertemporal decisions (e.g., should I smoke today?) into a single choice (e.g., should I smoke this month?). In this brief review, we succinctly summarize delay discounting and how it has been linked to lapses in self-control, using substance use as an exemplar. Next, we describe how choice bundling may theoretically work to counter excess discounting rates. Finally, we review the extant empirical research on choice bundling and offer recommendations for future research.